Environmental citizenship among pre-service teachers in Malaysian teachers training colleges - Ho, Yuek Ming (2007)
Environmental citizenship among Malaysians is generally known to be lacking. Thus, the implicit role of teachers as environmental citizenship role models implicates the need for pre-service teachers to acquire desirable characteristics of the model environmental citizen. The environmental education (EE) program in the Malaysian Teachers Training Colleges is expected to achieve the objective of molding model environmental citizens. In this research, theories and concepts underlying environmental education were integrated in a conceptual framework to contextualize environmental citizenship. A descriptive survey was conducted to assess environmental citizenship and its contributive factors among 2,728 pre-service teachers from ten selected Malaysian Teachers Training Colleges throughout Malaysia. Environmental citizenship level among the pre-service teachers was found to be moderate, with improvement needed for many of the environmental citizenship contributive variables. All the contributive variables, identified as environmental behavior, environmental attitude, environmental knowledge, sources from which information about the environment is obtained, and participation in environmental activities were positively correlated with environmental citizenship disposition. It was found that five of the factors contributed significantly towards environmental citizenship. Comparison made between pre-service teachers who were exposed and those not exposed to the EE program during teacher training showed that the former had significantly higher scores in environmental knowledge and environmental behavior. Graduate pre-service teachers were found to fare better in most variables compared to their non-graduate counterparts. Male pre-service teachers were found to have higher scores in environmental knowledge but lower in environmental attitude and behavior than their female counterparts. It is concluded that the EE Program implemented in the Malaysian Teachers Training Colleges is effective in disseminating environmental knowledge but not in developing environmental attitudes. The EE Program enabled preservice teachers to source for information but did not empower them to participate in decision-making nor to take action for a better environment. It is suggested that the EE Program incorporates more participative activities and experiential learning to inculcate desirable environmental citizenship attributes among future teachers to empower them in the crusade towards a better environment, and they in turn could empower the next generation of environmental citizens.